Internacionalização de bandas brasileiras nos anos 1980 e 1990 : que fatores os levaram ao sucesso internacional num mundo anterior à internet - Kuhar, Alan Jezovsek (2020)
Music is part of the culture of any population and it is no different in Brazil. The country has different musicians from different eras and styles that have gained international recognition. However, only in the 1980s, some Brazilian bands achieved an unprecedented feat until then: to achieve international recognition first, selling more records in the 1980s and 1990s abroad than in Brazil. This research is a multiple case study that presents a conceptual model that explains how the bands Sepultura, Viper, Dr. Sin and Angra went international before exploring the domestic market, selling thousands of records in the international market, then considered distant countries then as Japan and Germany, in a world where the Internet was a tool used by only few institutions. Supply Chain Management, Innovation, Strategic Relationship Networks, Resources Based View and Born Global were the theorical references developed in this thesis, which served as the basis for the construction of the interview script, essential tool for the progress of qualitative research, that was applied to 14 different people in the musical environment as members of the four studied bands, musicians from other Brazilian bands, music producers, music entrepreneurs and record company executives. To triangulate the study, 17 interviews of the studied bands performed on television programs made in the late 1980s and early 1990s were also selected and transcribed. Finally, the analysis of the selected material through Discourse Analysis, allowed the development of a model that makes it possible to explain which factors were decisive for the internationalization of the four bands even before the young musicians were recognized in Brazil. The Born Global attitude and the integration with several Strategic Relationship Networks were the foundations that led the young musicians to international recognition.